2014
DOI: 10.1371/journal.pone.0096776
|View full text |Cite|
|
Sign up to set email alerts
|

Chemical Genomic-Based Pathway Analyses for Epidermal Growth Factor-Mediated Signaling in Migrating Cancer Cells

Abstract: To explore the diversity and consistency of the signaling pathways that regulate tumor cell migration, we chose three human tumor cell lines that migrated after treatment with EGF. We then quantified the effect of fifteen inhibitors on the levels of expression or the phosphorylation levels of nine proteins that were induced by EGF stimulation in each of these cell lines. Based on the data obtained in this study and chemical-biological assumptions, we deduced cell migration pathways in each tumor cell line, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…Moreover, berberine-down-regulated EGFR activation stimulated by EGF led to a reduction in phosphorylated EGFR expression in prostate cancer PC-3 cells [ 39 ], which supported our findings. Our results showed no significant increase in Akt and p-Akt expression after EGF induction, which correlated with a previous study that reported the level of p-Akt in A431 cells was relatively stable after EGF induction [ 40 ]. Although there was no significant difference, p-Akt expression tended to increase after EGF induction and decrease with pretreatment with 13-butoxyberberine bromide.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, berberine-down-regulated EGFR activation stimulated by EGF led to a reduction in phosphorylated EGFR expression in prostate cancer PC-3 cells [ 39 ], which supported our findings. Our results showed no significant increase in Akt and p-Akt expression after EGF induction, which correlated with a previous study that reported the level of p-Akt in A431 cells was relatively stable after EGF induction [ 40 ]. Although there was no significant difference, p-Akt expression tended to increase after EGF induction and decrease with pretreatment with 13-butoxyberberine bromide.…”
Section: Discussionsupporting
confidence: 93%
“…Signaling pathways that regulate cell migration are complicated, therefore, the mechanisms regulating cell migration have remained largely unclear. We have previously addressed the mechanism by which EGF induces cancer cell migration [15,16]. Based on a chemical genomic-based pathway analysis for EGF-mediated signaling in various migrating cancer cells, we reported that common and cell-type specific pathways existed during EGF-induced cell migration [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…We have previously addressed the mechanism by which EGF induces cancer cell migration [15,16]. Based on a chemical genomic-based pathway analysis for EGF-mediated signaling in various migrating cancer cells, we reported that common and cell-type specific pathways existed during EGF-induced cell migration [15,16]. Moreover, we revealed that the 5-lipoxygenase/leukotriene receptor 1/cysteinyl leukotriene receptor 1 signaling pathway-mediated Tiam1 expression is involved in EGF-induced cell migration in A431 cells [17,18].…”
Section: Introductionmentioning
confidence: 99%